Expression of the HPV11 E2 gene in transgenic mice does not result in alterations of the phenotypic pattern - Leykauf, Kerstin; Kabsch, Kirsten; Gaßler, Nikolaus; Gissmann, Lutz; Alonso, Angel; Schenkel, Johannes (Transgenic research, 2008)
The E2 early protein of human papillomaviruses (HPV) has been found associated with the mitotic spindle therefore being implicated in the partition of the replicated viral DNA to daughter cells. In addition, E2 proteins bind to the upstream regulatory region of the virus and to cellular promoters modulating thereby cellular transcription and differentiation. In many cervical cancers, the E2 reading frame is interrupted upon incorporation of the viral genome into the host DNA. This results in the loss of the E2 mediated transcriptional repression and uncontrolled expression of the viral oncogenes. All these results have been obtained in transfected cells but no information is available on the E2 effects in the context of the entire organism. Transgenic mice were generated expressing the E2 protein of HPV11 under the control of the Ubiquitin C promoter. E2 mRNA is present in all mice tissues analysed and the E2 protein expressed in the skin (the target tissue of HPV11) was shown by Western blotting, albeit at a very low level. Analysis of the transgenic mice shows no major histological changes in the skin or all other tissues investigated. These data indicate that in transgenic mice the human papillomavirus type 11 E2 does not grossly modulate cellular proliferation or differentiation events.